Descriptive Analysis in the Implementation Strategy of Moving Class on Economy Subject at Islamic High School - Nelvia Ibrahim; Nurasmawi Nurasmawi; Desita Sari; Novian Aldo (STAI Hubbulwathan Duri, 2022)
The research was purposed to find how the implementing strategy of Moving Class that can be implemented by teachers in providing a good stimulus for student progress and development, This study only consists of one variable, that is Implementing Strategy of Moving Class on Economy Subject. The research used qualitative descriptive method with percentage, data collected by observation the main data to be encoded. While the interview and documentation were supporting data and supporting the ongoing research made. As for the subject in this study is one economic teacher of X IIS class, While the object of this research is how the moving class implementation strategy. From the findings of research, it was concluded that the implementing strategy of Moving Class on Economy Subject at State Islamic Senior High School 1 Pekanbaru was categorized